Analisis dan Desain Sistem Pendukung Keputusan Penilaian Kinerja Pegawai dengan Metode Analytical Hierarchy Process (AHP) - Taufiq, Rohmat; Sulkhan, Sulkhan; Yulianti, Yulianti; Saifudin, Aries (Jurnal Informatika Universitas Pamulang, 2020)
The decision support system (DSS) for employee performance appraisal is a decision support system used in the employee performance appraisal process at PT. Surya Toto Tbk. Currently, the employee performance appraisal process is still done manually (paper based) so that the reports produced are not real time. From the existing problems, this research aims to analyze and design a decision support system according to the existing criteria using the Analytical Hierarchy Process (AHP) method with the aim of being able to be developed into a Web-based DSS. The method used begins with communication with management, especially the perpetrators of employee performance appraisals. Furthermore, planning, data collection process, analysis, design and finally making reports are carried out. The conclusion of this study provides a suggestion for the addition of subcriteria from the existing criteria. After calculating with AHP, the value that appears for the work outcome criteria (A) on the quantitative subcriteria A11 with a score of 0.123, qualitative A12 with a score of 0.033, delivery A13 with a score of 0.024 and Implementation of SOP A14 with a score of 0.018. The score is for a very good value (BS).